Peran Teacher Quality Dalam Memediasi Pedagogical Competence, Dan Teacher -Student Relationship Terhadap Teacher Perform Pada Guru Bahasa Inggris Smp Swasta Dan Mts Swasta Kota Serang - pratama, Muhammad Rifki (Center of Language and Cultural Studies, 2023)
This research is to find out whether there is a direct influence of pedagogical competence on teacher quality, whether there is an influence of teacher student relationship on teacher quality, whether there is a direct influence of pedagogical competence on teacher performance, whether there is a direct influence of teacher student relationship on teacher performance, whether there is a direct influence of teacher quality on teacher performance, whether there is an indirect influence of pedagogical competence on teacher performance through teacher quality, whether there is an indirect influence of teacher student relationship on teacher performance through teacher quality in English teachers of private junior high schools and MTs in Serang City, The purpose of this study is to find out, the direct effect of pedagogical competence on teacher quality, the effect of teacher student relationship on teacher quality, the direct effect of pedagogical competence on teacher performance, the direct effect of teacher student relationship on teacher, the direct effect of teacher quality on teacher performance, the indirect effect of pedagogical competence on teacher performance through teacher quality, the indirect effect of teacher student relationship on teacher performance through teacher quality in English teachers in junior high schools and private MTs in Serang City. To achieve this research, researchers used quantitative methods with analytical tools in the form of SEM and Smart PLS tools. For a population of 148 teachers with a minimum sample size of 106 using non probability sampling. The results showed that the influence of pedagogical competence, teacher student relationship, teacher quality, teacher perform affiliated well perceived by the teachers so that there is a positive and significant influence on all variables that are interconnected with each other.